Detection of antimicrobial resistance in bacterial pathogens from aquaculture ponds using poultry waste - Keerthana, K. M. (KUFOS, 2019)
The emergence of antimicrobial resistance (AMR) in bacterial pathogens is a major public health concern, and the practice of feeding poultry wastes in aquaculture farms can turn out to be one of the contributors to the AMR burden. The prevalence of AMR bacteria in selected aquaculture farms of Kerala where poultry waste was being dumped in the ponds were assessed in order to highlight the consequences of feeding poultry waste to fish. Majority of the farmers are unaware that antibiotics used as growth promoters and as prophylactic in poultry could drive antimicrobial resistance in isolates in their farms and thus, the environment. Bacteria were isolated from soil, water, and fish from 11 selected fish farms to analyse their antibiotic resistance and evaluate the exerted antibiotic pressure on the nearby environment. Out of 11 aquaculture farms, 8 farms used raw poultry waste as feed, 2 farms used cooked poultry meat, and one farm followed normal recommended fish feed. The isolates were identified by their morphological characteristics and conventional biochemical tests. Antibiotic susceptibility of selected isolates was examined against 32 antibiotics using Kirby-Bauer disc diffusion method. MAR index value of 10 farms ranged from 0.21 to 0.68 which indicates high risk source of antibiotics from poultry waste. The results showed that as compared to aquaculture farms fed with normal diet and cooked poultry waste, high antibiotic resistance prevalent among indigenous bacteria is of high concern in aquaculture farms fed with raw poultry waste. Moreover, it also badly affect the water quality parameters of the farm and the surrounding environment.